BURNOUT AS AN “OCCUPATIONAL PHENOMENON” AMONG HEALTHCARE WORKERS AND COPING STRATEGIES – A REVIEW OF LITERATURE - Hanna Paszkiewicz; Oliwia Gugała; Kamil Nowak; Alicja Stryczek-Schlusche; Patryk Kowalczyk; Bartłomiej Trzciński; Igor Winogrodzki; Aleksandra Magdalena Furczyńska; Filip Bracichowicz; Aleksandra Gęsińska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Burnout is a syndrome that has become a major problem in modern, hectic lives. It is scientifically proven that the medics report higher level of burnout than any other working field. It has been recognized as a exhaustion, depersonalization and decreased satisfaction and efficiency at work. It leads to severe states like depression, anxiety and permanent weariness. It can cause drastic deterioration in the health care system and have negative consequences for the patients. Therefore, we undertook this study to investigate the scale of the problem.Materials and Methods: A detailed review of literature was conducted to investigate the problem of burnout and to focus on possible coping strategies using PubMed, Google Scholar and MEDLINE databases.Keywords: burn-out, medical burn-out, occupational stress, coping strategies, physicians, medical students, mindfulness, exhaustion, occupational burn-outResults: Data shows that 50% of physicians are affected by burnout syndrome. Documented symptoms are both mental and physical, most common are depression, anxiety and lack of work satisfaction. The scale of the suffering healthcare workers reached its peak during COVID-19 pandemic. Women declared higher levels of burn-out, comparing to male coworkers. The problem occurs at the early stages of medical career, as around 20% of medical students declared adequate symptoms.Conclusions: Burn-out phenomenon must be taken under further research, as it becomes worldwide health issue among healthcare workers. It is essential to spread awareness, encourage medics to seek for professional help and collect a significant amount of data to prepare a concrete strategies and treatments programs.